Physical, Chemical, Biological properties and fish species type of Geray reservoir, -W/Gojjam Zone, Ethiopia - Brehan Mohammed; Dereje Tewabe; Wonde Zelalem; Adane Melaku (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2016)
The aim of the present study was to determine the physical, chemical and biological characteristics and to characterize the fishery of Geray reservoir. Three sites from the inlet site, the open water and the outlet has been selected and samples were collected using YSI 556MPS model multimeter and Palin test photometer 5000 .Temperature, pH, dissolved oxygen, salinity, Total Dissolved Solid, conductivity, secchi disk measurement, alkalinity, nitrate, phosphate, ammonia and turbidity were the parameters measured. Plankton sample collected using 55 and 80 micrometer mesh net. The most abund taxon was copepoda (666 ind. /m3 of water with their juvenile stages "Nauplia" or contributed 85% of total zooplankton taxa), which was followed by Cladocera (190 inds. /m3 or 15%). Among the 3 study sites the open water site showed higher density of zooplankton, especially cyclopod followed by outlet site.The inlet site was relatively low in zooplankton density. Cyprinus carpio, Varicorhinus Beso, Carasius Auratus and Oreochromis niloticus were species found in the reservoir. Almost all the physical and chemical parameters sampled of this reservoir water were within desirable limits for aquatic biodiversity the current state of the water quality of the reservoir is conducive for fish production. But the current management is not good for its sustainability, knowingly or unknowingly the activities done on and around the reservoir will shorten the sustainable utilization of the reservoir. The community should be awaked while they are starting to overexploit the resource.